Respuestas

2014-01-20T14:13:28+01:00

y2 + 3y - 550
La factorización de esta expresión es de la forma:/
        (y + a)(y - b)
                  donde:
                    a - b = 3
                    a x b = -550
Descomponiendo 550 en sus factores primos
550/2
275/5
  55/5
 11/11
   1             550 = 10 x 55
                         = 22 x 25
                         = 55 x 11
De aqui se deduce:
               a = 25
               b = - 22
Luego:
             y2 + 3y - 550 = (y + 25)(y - 22)   RESULTADO FINAL